Georgy Chelpanov. On the edge of psychologism and traditional approach. - Myroniak Віталія (Actual Problems of Mind, 2024)
The central inquiry of this article is of significant importance: What was the predominant trajectory in Georgy Chelpanov’s logical evolution? This investigation delves into the prevalent approaches to logic at the turn of the 19th and 20th centuries: mathematical logic, psychologism in logic, and the traditional approach to logic. Mathematical logic, often called the "new logic," arose as a response to metaphysical influences on logic. Therefore, this "new logic" rejects metaphysical influences and moves towards algebra. On the other hand, psychologism in logic remains in this period. Although more logical directions can be found in this period (for example, "epistemological" is often indicated), I focus on three. Furthermore, the third, the last, but not the last in terms of its influence and prevalence among scientists, is traditional. Here, we are talking about the general presentation of logic, which is inherent in the university and dates back to the Middle Ages. Adepts in this direction are most interested in questions about concepts, judgments, reasoning, etc. So, to what direction can the logical development of Georgy Chelpanov be attributed? On the one hand, there is a desire to count the researcher among the supporters of psychologicalism in logic because during his "kyiv period," he founded the first psychological laboratory in 1897. Also, in his work "Textbook of Logic," Georgy Chelpanov often uses terminology inherent in psychology. On the other hand, Chelpanov repeatedly points out that psychology should not influence logic. Moreover, he suggests considering logic as a normative discipline. In conclusion, Georgy Chelpanov is at the junction of psychologism and the traditional approach. He is not a supporter of strong psychologism, but his writings have manifestations of weak psychologism. As for the traditional direction, the textbook by Georgy Chelpanov is a vivid example of this approach, starting with the structure and topics the author considers and ending with the definitions offered there. The article also describes the scientific environment, which in the mentioned period was subject to several prohibitions due to the occupation of the russian empire, which also affected the development of logic or any other science.